2014
DOI: 10.1111/cas.12453
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of c‐MET expression and genetic mutational status in colorectal cancer patients after liver resection

Abstract: c-MET is implicated in the pathogenesis and growth of a wide variety of human malignancies, including colorectal cancer (CRC). The aim of the present study was to clarify the association between c-MET expression and tumor recurrence in CRC patients after curative liver resection, and to evaluate concordance in c-MET expression and various mutations of KRAS, BRAF and PIK3CA between primary CRC and paired liver metastases. A cohort of patients was tested for c-MET immunoreactivity (i.e. immunohistochemistry [IHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…Therefore, it would be reasonable to expect that the frequency of cases with MET overexpression would be higher in the later (73% versus 22%). Similar effect occurred in CRC comparing Voutsina et al 54 , Ma et al 49 and Shoji et al 56 studies. In NSCLC, MET overexpression was reported by Spigel et al 61 in 52% and by Masuya et al 32 in 41% of the patients.…”
Section: Molecular Mechanisms Of Met Activation In Carcinogenesissupporting
confidence: 69%
See 1 more Smart Citation
“…Therefore, it would be reasonable to expect that the frequency of cases with MET overexpression would be higher in the later (73% versus 22%). Similar effect occurred in CRC comparing Voutsina et al 54 , Ma et al 49 and Shoji et al 56 studies. In NSCLC, MET overexpression was reported by Spigel et al 61 in 52% and by Masuya et al 32 in 41% of the patients.…”
Section: Molecular Mechanisms Of Met Activation In Carcinogenesissupporting
confidence: 69%
“…IHC was the common technique used to determine MET expression. Overexpression of the MET protein has been more commonly investigated in various solid tumors as seen in Table 2 , with studies in bladder 45 , breast 37 - 39 , 46 - 51 , colorectal 49 , 52 - 56 , gastric 57 , hepatobiliary 58 , head and neck 42 , 43 , lung 32 , 49 , 59 - 61 , ovarian 49 and renal 49 , 62 cancers.…”
Section: Molecular Mechanisms Of Met Activation In Carcinogenesismentioning
confidence: 99%
“…Seven of the 14 studies included in the systematic literature review reported RFS. Multivariable Cox regression analysis was performed for all seven studies, and the HR data were pooled in a separate meta‐analysis ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…3). The seven studies reported a total of 906 patients undergoing resection of CLM; in these patients the KRAS Petrowsky et al 19 Nash et al 16 Stremitzer et al 13 Huang et al 20 Umeda et al 23 Vauthey et al 14 Karagkounis et al 12 Kemeny et al 24 Overall (I 2 = 0·0%, P = 0·965) Cejas et al 18 Isella et al 21 Stremitzer et al 13 Shoji et al 25 Vauthey et al 14 Karagkounis et al 12 Kemeny et al 24 Overall (I 2 = 0·0%, P = 0·997)…”
Section: Kras Mutation and Recurrence-free Survivalmentioning
confidence: 99%
“…(9)(10)(11) Previous reports showed that HGF could induce EMT in PDAC cells; moreover, the HGF receptor, c-Met, was identified as a dominant pancreatic CSC marker. (14) Therefore, it was expected that c-Met expression of PDAC can be a prognostic marker despite no report assuming that, and actually, c-Met expression was previously identified as an indicator of poor prognosis in various cancers, (32,33) and a c-Met inhibitor was developed as a candidate drug for treating advanced hepatocellular carcinoma. (34) Our results firstly elucidated the role of c-Met expression in PDAC.…”
Section: Discussionmentioning
confidence: 99%